Effect Size Of Pakem Model Implementation In Mathematic Learning On Improving Student’s Problem-Solving Mastery On Function Material At Junior High School - Jafri, Fauzan (Universitas Riau Kepulauan, 2016)
This research is motivated by the level of junior high school students' mathematical problem solving was still low. Based on the preliminary study which conducted by one of the schools in Batam shows the average score for mathematics was 62 for 100 scale. The purpose of this study is to obtain and investigate the improvement of students' problem-solving mastery on relations and functions material as the effect of PAKEM model. The research method which used is pre-experiment and with one group pretest-posttest design. The subjects of this study were VIII grade students of one of the first junior school in Batam at odd semester 2015-2016 academic year, totally 32 students. Sample of this research were taken by random sampling technique. Students’ problem solving mastery was measured by using problem-solving test, whereas the students’ problem-solving mastery improvement between before and after the concept of effect size implementation was calculated to find the effect size of applying the PAKEM model. The result showed that the effect size of applying the PAKEM model on improving problem solving mastery is 3.3, it means, the PAKEM model implementation on improving problem-solving mastery on function has a strong influence. It can be concluded that the PAKEM model implementation can improve problem solving mastery.